Dynamics of cognitive performance at rest and after exhaustive exercise in top-three world-ranked mixed martial arts athletes: a series of case studies - Faro, H. K.; de Souza Fortes, L.; Gomes da Silva Machado, D. (The Journal of Sports Medicine and Physical Fitness, 2020)
Cognitive performance plays a key role in sports performance, especially in combat sports such as mixed martial arts (MMA). Studies with active and sedentary individuals showed either no change or decreased cognitive performance during or immediately after exercise. However, it is possible that elite MMA athletes would present preserved/improved cognitive performance after exhaustive exercise. In this series of cases studies, we tested this hypothesis by submitting three elite MMA athletes from the Bellator MMA® and UFC® to a cognitive assessment before, immediately after and 15 min after exhaustive exercise. A modified computerized version of the Stroop Test was used to test cognitive inhibition performance, from which reaction time (RT) and accuracy were obtained. The athletes performed an incremental exercise on a cycle simulator until volitional exhaustion. Immediately after exercise RT improved consistently in all three athletes (-6.5%; -8.0%; -15.0%), while accuracy presented a small increase (2.6%), decreases (-3.8%) or no change. Fifteen minutes after exercise, RT remained improved in two athletes (-9.1% and -15.5) or slightly increased (0.4%), while accuracy presented small increase in all athletes (0.5%; 1.3%; 2.1%) compared to pre-exercise. This result indicates that elite MMA athletes may present improved cognitive performance immediately after exhaustive exercise, which suggests that cognitive-motor training for MMA should be considered when planning a training program.